POLA ASUH KELUARGA TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI LINGKUNGAN KELUARGA POLRI - Susanti, Esti Nurwita; Ansori, Ansori; Widiastuti, Novi (IKIP Siliwangi, 2024)
Family parenting on the social emotional development of children in the Polri family environment, the purpose of this study is to find out how the parenting pattern in the Polri family environment and to find out whether family parenting has an impact on children's social relationships outside the dormitory. In accordance with the objectives that have been formulated, the population in this study is 10 Polri families who live in the West Java Police SPN dormitory. The author took samples using purposive sampling, amounting to 6 families. The data collection instruments of this research were in the form of observation, interviews and documentation. In analyzing the data using a qualitative descriptive method. The results of the research on parenting patterns on the social emotional development of children in the Polri family are 64.96%, so it is categorized in the Good Parenting Pattern in the Police Family. The parenting style applied in the police family is the Democratic Parenting Pattern. The impact of Parenting on children's social relations outside the dormitory which is dominantly carried out by children of Polri families is that they are dominant in being polite to their elders, giving smiles to friends who greet, and greeting each other when they meet each other. From this categorization, it shows that the impact of family parenting on children's socio-emotional social development is included in the Good category.